Analisis Nilai Moral dalam Buku Kisah Batu Menangis - Damayanti, Anggita; Ridho, Ais Habibatur; Muttaqin, Aufan; Mas’odi, Mas’odi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This research aims to examine the moral values in Batu Menangis folklore through a qualitative approach based on literature study. The Batu Menangis folktale, which originated from Indonesian culture, contains profound moral messages, especially about the importance of humility, respect for parents, and the adverse effects of pride. This research method uses a literature study analysis approach that focuses on collecting and analyzing data from various literatures, including the main text (Kisah Batu Menangis) as well as other supporting references. Data were obtained from various literature sources, such as relevant folklore books, journals and cultural articles. The analysis was conducted using a thematic approach to identify moral messages contained in the storyline, characterization of characters, and conflicts that occur. The results show that this story teaches three main values: (1) respect for parents as the basis of social life; (2) self-awareness of human limitations as the essence of humility; and (3) the consequences of pride, which brings suffering and destruction. This research confirms the importance of folklore as a medium for moral education that is relevant in modern life. The Batu Menangis story is also recommended as teaching material to build the character of the younger generation, especially in terms of respect for family and humility.